2014
DOI: 10.1007/s10067-014-2569-3
|View full text |Cite
|
Sign up to set email alerts
|

In palindromic rheumatism, hand joint involvement and positive anti-CCP antibodies predict RA development after 1 year of follow-up

Abstract: This study aimed to determine the frequency of rheumatoid factor (RF) and cyclic citrullinated peptide (CCP) antibodies in a cohort of patients with palindromic rheumatism (PR) and to find determinants for progression to rheumatoid arthritis (RA). All new cases of PR (n=90) were included prospectively and followed up for 1 year, and a comparison group of RA cases (n=70) was also included. At study entry in all patients in both groups, RF and anti-CCP antibodies were tested, and the findings were compared and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 26 publications
(37 reference statements)
0
31
0
Order By: Relevance
“…PR is characterised by intermittent flares of articular and periarticular inflammation. Up to 50% of patients with PR will eventually develop rheumatoid arthritis (RA), with those that are anticyclic citrullinated peptide (CCP) antibody positive at highest risk of progression 2–4. However, the time to progression is variable and many anti-CCP positive patients with PR do not develop persistent arthritis, even after several years of follow-up 5.…”
mentioning
confidence: 99%
“…PR is characterised by intermittent flares of articular and periarticular inflammation. Up to 50% of patients with PR will eventually develop rheumatoid arthritis (RA), with those that are anticyclic citrullinated peptide (CCP) antibody positive at highest risk of progression 2–4. However, the time to progression is variable and many anti-CCP positive patients with PR do not develop persistent arthritis, even after several years of follow-up 5.…”
mentioning
confidence: 99%
“…Few studies have quantified patient symptoms preceding ERA diagnosis or characterized PR preceding ERA . The strengths of this study are its unique quantitative characterization of episodic inflammatory symptoms prior to ERA and inclusion of ERA patients from multiple centers.…”
Section: Discussionmentioning
confidence: 99%
“…Palindromic rheumatism (PR) constitutes transient acute attacks of self‐resolving articular and/or periarticular inflammation without radiographic damage . Although it is debated whether PR is part of the spectrum of rheumatoid arthritis (RA), estimated rates of PR progression to RA range from 50% to 67%, and PR is widely considered an at‐risk phenotype for development of RA .…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-sectional analysis of a Spanish PR cohort, the frequency of anti-CCP antibodies was similar in PR compared with early RA patients (53% vs 55% respectively) (6). Other international PR cohorts report similarly high frequencies of anti-CCP positivity (between 46% and 68%) (7)(8)(9)(10)(11). A notable outlier is a recently described Taiwanese PR cohort where only 11/84 (13%) of patients were anti-CCP positive and 12/84 (14%) were RF positive (12).…”
Section: Is Pr Simply Relapsing-remitting Ra?mentioning
confidence: 95%
“…PR and RA have a predilection for the same joints. Studies of different PR cohorts have consistently reported the wrists, metacarpophalangeal joints (MCPJs) and proximal interphalangeal joints (PIPJs) as the most commonly affected sites in PR (2,4,8,9,19,20). In contrast, the spine and sternoclavicular joints are the least frequently affected sites (mean 4% and 2% of patients respectively) (19).…”
Section: Clinical Featuresmentioning
confidence: 99%